DETERMINATION OF INDOOR AND OUTDOOR AIR QUALITY UNDER DIFFERENT VENTILATION CONDITIONS IN A RESIDENTIAL AREA OF LAHORE, PAKISTAN - M. Abbas; S. Razzaq; R. Shahzadi; A. Rahman; F. Manzoor; Z. Ali (Journal of Animal and Plant Sciences, 2015)
Indoor air quality is not only determined by indoor sources but outdoor sources also contribute to it. In this study, a real time aerosol monitor was run parallel in a room and outdoors to measure the mass concentrations of PM with a view to 2.5 investigate role of ventilation on indoor PM Under high ventilation conditions, difference in mass concentration of 2.5. PM of indoor and outdoor air was negligible. The indoor and outdoor 24-h average values of PM were 86.72µg/m3 2.5 2.5 3 and 80.42µg/m respectively. However, there was a visible difference in the average concentrations of particulate matter 3 in outdoor air and indoor air under low ventilation available. The 24-hour mean value was recorded to be 172.45µg/m 3 indoors while it was only 108.26µg/m outdoors. This high value indoors was also due to the presence of a smoker in the room. The indoor concentration was strongly correlated with the outdoor air when the available ventilation was high (r = 0.863) and weakly correlated when ventilation was low (r = 0.184). It was concluded that under high ventilation conditions, indoor air is majorly determined by infiltration of the outdoor air, while when ventilation is very low, indoor sources rather than outdoor define the indoor air quality. particles at different sites. The results showed that
Keywords: Different ventilations; Indoor air quality; residential areas; Pakistan.